UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA MATERI BILANGAN DENGAN MODEL PEMBELAJARAN PBI (PROBLEM BASED INSTRUCTION) PADA KELAS VII SMP N 21 KOTA BENGKULU - sutikno, lugu; Herawaty, Dewi; Susanta, Agus (JP2MS, 2018)
The aim of this study was to find out how to improve activities and students’ learning outcomes by applying PBI (Problem Based Instruction) Learning Model. This study was a classroom action research that the technique of data collection was by using activity observation sheets and test of students’ learning outcomes. The research subject was class VII.7 SMPN 21 of Bengkulu City academic year of 2017/2018 with 28 students in total consisted of 14 male and 14 female students. The data collected descriptively used the mean score of the students’ activities, the average of the students’ score and the students’ mastery learning. The process done by the researcher was that the teacher gave example of story problem related to daily life. The teacher formed study groups consisted of 4-5 students. The group formation was varies based on the ability (pre-test) and gender. The teacher helped the groups facing difficulties and observed the discussion activity in solving the problems. The teacher asked one of the groups to present the result in front of class. Based on the research result, it could be concluded that the implementation of PBI (Problem Based Instruction) could improve the activities students’ learning outcomes.Key Words: Activities, PBI (Problem Based Instruction)